Water-soluble bis-triazolyl benzochalcogendiazole cycloadducts as tunable metal ion sensors - Bryant, Jonathan; Lindner, Benjamin; Bunz, Uwe H. F. (The journal of organic chemistry, 2013)
A series of bis-triazolyl benzochalcogendiazoles was synthesized to investigate their metal-binding capabilities. These fluorophores were formed through the cycloaddition of an ethynylated benzochalcogendiazole and a water-soluble azide. Variation of the chalcogen heteroatom was seen to affect the photophysical properties as well as the metal-binding activity. These cycloadducts exhibited a distinct response to Cu2+, Ni2+, and Ag+ in water. The binding affinity for the copper and nickel ions increased moving the chalcogen atom from O to Se. Statistical analysis of the spectral data enabled differentiation of Ag+, Cu2+, and Ni2+ ions.